Variability of Solar UV Index in Nepal - Sharma, Niranjan Prasad (Journal of the Institute of Engineering, 2017)
The paper presents the variability of solar UV index in main cities of Nepal. The latitude and longitude of the cities are (27.72°N, 85.32°E), ( 28.22°N, 83.32°E) and (26.45°N 87.27°E) are located at an elevation of 1350m, 800m and 72m respectively from the sea level. The NILU- UV irradiance meter of serial number (135, 137 and 133) was used to record UV radiation on these stations. From the measurement and data analysis it was found that there were distinct diurnal, hourly mean and spring variations in the UV index. The UV index is primarily controlled by solar zenith angle for both the diurnal and seasonal variations. The highest values of hourly mean UV index was found at noon time in all seasons. Atmospheric parameters such as Solar Zenith angle (SZA), Cloud cover, aerosols and Ozone contribute to the daily fuctuations in the UV Index. The UV Index was found to be 8.72, 9.9 and 9.2 in June 9, in Kathmandu (KTM), Pokhara (PKR) and Biratnagar (BRT).While the UV Index (UVI) in September 27 was found to be 8.52, 8.18 and 9.36 in KTM, PKR and BRT respectively. Daily mean highest UV Index before monsoon at PKR was found to be 10.6 and 8.98 at day number 144 and 100. Journal of the Institute of Engineering, 2016, 12(1): 114-119